STUDY OF THE EFFECTS OF INCLINATION ANGLE OF ARCHIMEDES TURBINE CHARACTERS - GENERATOR STUDY - Dede, Markurius Hariyadi; Danial, Danial; Taufiqurrahman, Muhammad (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
The current demand for electrical energy stands as a crucial aspect in both household and industrial contexts. Indonesia, blessed with abundant water resources, holds significant potential in the development of renewable energy. Specifically, West Kalimantan boasts plentiful rivers that serve as potential sources for electricity generation. The Archimedes Turbine has emerged as a primary focus for generating electricity from water flow. This research aims to analyze the evolution of the Archimedes turbine concerning its characteristics with angle variations and their influence on the generator. Through a literature review, this study explores the development of Archimedes turbines over time.In this analysis, the variation in the turbine's angle of inclination concerning the generator takes center stage. The research findings indicate that the performance characteristics of the Archimedes turbine, such as efficiency, generated power, and torque, are evaluated under various angle conditions. This research is expected to provide profound insights into the contribution of Archimedes turbine technology in the future and expand the understanding of its potential application in different water contexts.The research findings reveal that the optimal turbine performance concerning water flow occurs at a 30Ëš angle with a flow rate of 100% (Q3 = 0.006 m^3/s). Under unloaded conditions, the turbine produces a voltage of 19.13 V, while under loaded conditions, the resulting voltage is 17.21 V.